The Implementation Of Moral Values In Surah Al-Hujurat Verses 11-13 As The Basis For “Stop Bullying” Habituation At MI Baitur Rohman Asemrowo Surabaya - Wila, Wilayatul Istianah, S.H. (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2025)
Bullying is a social problem that often occurs in educational settings and can have a negative impact on students' psychological development. In Islam, the moral values contained in the Qur'an can be used as guidelines to shape the character of students to get used to behaving well and avoiding actions that harm others. This study aims to examine the implementation of moral values in Surah Al-Hujurat verses 11-13 as the basis for habituation